Milan and its lost river: when surviving images represent unique narrations of invisible relationships - Oldani, Andrea (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2021)
One of the most predictable implications of photography consists of the ability to fix some images returning them in a variable timeframe for the observation. In all the major world cities, it is common to incur in some book where recent photos are compared to old ones searching the same point of view in order to make the comparison more accurate and stimulate the critical ability of the observer. An exercise that sometimes stimulates a sort of regret for the past, pointing out a diffused excess of nostalgia for times gone by. Nevertheless, the reality and meaning of modern city images are not always so prosaic. What happens when photographs are evocative of a reality that is completely lost in the collective imaginary even though it still exists and functions, despite being forgotten and buried in the depths of the city? This is the case of very few pictures capable of telling the story of a city, Milan, and its only “real” river, the Olona, whose waters, humiliated and rejected, continue to flow in total amnesia. It is a different story when photography does not have the role of nourishing nostalgia, but the power to make visible and explain the variation of a presence and its progressive obliteration. Some pictures testify to the passage from the bucolic amenity of the river and its banks in a pre-urban context to a muscular urban infrastructure. A rigid channelized river, shown with confidence, is trying to keep its presence, until the moment of its inevitable decline and disappearance. It is in these images that the possibility of reconsidering the Olona as a part of the new project for the city lies.